IoT-Based Training and Mentoring on Water Quality Management and Carp Health Management at UPR Dunia Air Jayapura - Indrayani, Ervina; Mantayborbir, Vyona; Agamawan, Lalu Panji Imam; Manalu, Khristopher A. A.; Numberi, Yulindra Margaretha; Izaac, Fransina A.; Pamangin, Lisda O. M. (Jurnal IPTEK Bagi Masyarakat, 2026)
Aquaculture of common carp (Cyprinus carpio) is a freshwater fishery commodity with high economic value and requires well-controlled water quality and fish health management. However, small- to medium-scale farmers still face limitations in continuous water quality monitoring. This community service activity aimed to improve the capacity of common carp farmers at Unit Pengolahan Air Dunia Air through training and mentoring on water quality and fish health management based on simple technology. The activity was conducted from September to October 2025 at Unit Pembenihan Rakyat Dunia Air, Koya Timur, Jayapura City. The methods employed included training sessions, discussions, hands-on practice mentoring, and the application of technology in the form of an Internet of Things (IoT)-based water quality monitoring device and a water quality control logbook. The IoT device was used to monitor water quality parameters in real time, while the logbook functioned as a tool for routine recording and evaluation. The results showed an increase in participants’ understanding of water quality management concepts, as indicated by their ability to identify key water quality parameters along with their optimal ranges. In addition, participants demonstrated improved skills in operating IoT-based monitoring devices and in routinely recording data in the water quality control logbook. Changes in aquaculture practices were also observed, including increased frequency of water quality monitoring and the implementation of fish disease prevention measures. The application of this technology promotes more controlled and sustainable common carp aquaculture practices.